A Study On The Usage Of M-Learning Applications Within Bulgarian Schools - Bonimir Penchev (Business & Management Compass, 2024)
The transformation of the educational model is directly linked to the key participants in the educational process. Modern pupils cannot imagine life without the usage of various digital technologies such as mobile devices. Moreover, today’s learners spend more time preparing for school using interactive mobile applications. That defines the purpose of this article: to explore the usage of m-learning applications in the educational process within Bulgarian schools. To achieve that it has been created a survey that consists of 11 questions and was distributed to 140 participants (pupils from Bulgarian schools). The results have shown that 54.28% of respondents use m-learning applications within the classroom and 72.86% of them use m-learning applications for self-study. Additionally, 60% of respondents believe that using such applications would enhance the educational process. This provides ample justification for directing efforts from all stakeholders (educational institutions, educators, and learners) toward wider and more comprehensive integration of these applications in the educational process. From the perspective of future research, there could be endeavors to conduct a more extensive and representative study by trying to utilize cluster sampling in order to overcome the limitations posed by the current research methodology.